PENGETAHUAN REMAJA PUTRI TENTANG FAKTOR PENYEBAB DAN PENCEGAHAN ANEMIA - Siagian, Joni; Silalahi, Amelia Dini Anggraini; Pane, Efi Irwansyah (LPPM AKPER GITA MATURA ABADI KISARAN, 2025)
Anemia is a condition where the number of red blood cells is lower than normal or anemia, one of which is caused by a lack of iron consumption. This study aims to determine the causes and prevention factors of anemia in adolescent girls. This research uses a descriptive survey and the research method is cross sectional. A total of 170 people at the Taladan Ujung Kubu Private Madrasah Aliyah as a population. The sampling technique used simple random sampling with a sample of 17 people. Data collection techniques include observation, interviews, documentation and filling out questionnaires using the categories of knowing and not knowing. The results of this study showed that knowledge of adolescent girls about the factors that cause anemia was 5.23 (58.1%)